2010
DOI: 10.1093/ndt/gfq419
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of dietary phosphorus restriction and phosphorus binders to target fibroblast growth factor 23 in patients with chronic kidney disease

Abstract: Background. High levels of fibroblast growth factor 23 (FGF23) are associated with mortality and progression of chronic kidney disease (CKD). Reducing dietary phosphorus intake lowers FGF23 secretion in healthly individuals, but there is little data on its effects in patients with pre-dialysis CKD. Methods. Using a 2 × 2 factorial design, we randomly assigned 16 normophosphataemic CKD stage 3-4 patients to receive a 2-week treatment with either lanthanum carbonate 1000 mg three times daily or placebo, and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 25 publications
7
119
2
4
Order By: Relevance
“…This contrasts with findings from prior studies of dietary phosphate restriction or phosphate binder use in CKD, which reported significant reductions in urinary phosphate excretion commensurate with the intensity of the interventions (9,13,15). Possible explanations for this lack of an effect are insufficient dietary phosphate restriction, lower doses of LC than in prior reports (15,17), withinperson variability in 24-hour urinary collections, and waning adherence with the interventions in later weeks of the study.…”
Section: Variablecontrasting
confidence: 94%
See 2 more Smart Citations
“…This contrasts with findings from prior studies of dietary phosphate restriction or phosphate binder use in CKD, which reported significant reductions in urinary phosphate excretion commensurate with the intensity of the interventions (9,13,15). Possible explanations for this lack of an effect are insufficient dietary phosphate restriction, lower doses of LC than in prior reports (15,17), withinperson variability in 24-hour urinary collections, and waning adherence with the interventions in later weeks of the study.…”
Section: Variablecontrasting
confidence: 94%
“…This fixed dose was chosen because it reduced urinary phosphate excretion safely and effectively in CKD stages 324 (13,15). Matching placebo was prescribed at the same frequency.…”
Section: Randomization Interventions and Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…23 Whether our disparate findings with C-terminal and intact FGF23 reflect better precision with the intact assay or true differential effects on both molecules is unknown. A similarly discrepant result between the C-terminal and intact FGF23 assays was described in 66 subjects with normal kidney function, in whom dietary phosphate restriction reduced intact FGF23 but had no effect on C-terminal FGF2.…”
Section: Discussionmentioning
confidence: 93%
“…They showed that dietary P restriction and lanthanum carbonate reduced urinary P excretion without changes in serum P and FGF23 (25). In contrast, the group assigned to a higher dietary P and placebo had a significant increase in FGF23 levels (32 Our study is the first to evidence that a conspicuous protein restriction (0.3 g/kg body wt per day), with essential amino acids and ketoanalogues and without the administration of phosphate binders, is able to reduce FGF23 in CKD patients not yet on dialysis (stages 3 and 4) compared with a usual LpD (0.6 g/kg per day). Healthy subjects have a P intake of about 1200 mg (31,35); the diets used in our study contained 350-420 (VLpD) and 600-700 (LpD) mg/d of phosphorus, with a reduced P intake of 68% and 34%, respectively, compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%